227k views
4 votes
(-6, -7) and (3, 4) Slope m = Y-Intercept

1 Answer

0 votes

We have to use the slope formula.


m=(y_2-y_1)/(x_2-x_1)_{}

Let's replace the given points in the formula.


m=(4-(-7))/(3-(-6))=(4+7)/(3+6)=(11)/(9)_{}

Then, we use the point-slope formula to find the equation.


\begin{gathered} y-y_1=m(x-x_1) \\ y-4=(11)/(9)(x-3) \\ y=(11)/(9)x-(11)/(3)+4 \\ y=(11)/(9)x+(12-11)/(3) \\ y=(11)/(9)x+(1)/(3) \end{gathered}

Hence, the y-intercept is 1/3

Remember that the y-intercept is always the independent term.

User ArthurGuy
by
5.5k points